2021
DOI: 10.19087/jveteriner.2021.22.2.262
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistant Pattern and Resistant Gene Identification of Staphylococcus aureus from Chicken Farm in Bogor

Abstract: Chicken is one of the important protein source in Indonesia. Moreover, the largest population of chicken layer and poultry in Indonesia is known situated at West Java province with Bogor manicipality as the main producer. The aims of this study were to determine the antibiotic resistance pattern of Staphylococcus aureus isolated from poultry and layer farm in Bogor. The study also identified gene encoded the resistance. Cloacal swab samples were collected from chicken broiler and layer farm in Bogor manicipali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
(31 reference statements)
0
4
0
3
Order By: Relevance
“…Staphylococcus is the most common bacterium that contaminates eggshells during the formation and laying process [37,38]. S. aureus contamination of eggs can occur horizontally when passing through the cloaca; this is reinforced by research [39] which found S. aureus in 28% of broiler cloacal swab samples and 50% of laying hens in Bogor Regency, Indonesia. Shells contaminated with many microorganisms will increase the risk of microbial penetration into eggs.…”
Section: S Aureus Contamination In Eggs and Egg Products In Indonesiamentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococcus is the most common bacterium that contaminates eggshells during the formation and laying process [37,38]. S. aureus contamination of eggs can occur horizontally when passing through the cloaca; this is reinforced by research [39] which found S. aureus in 28% of broiler cloacal swab samples and 50% of laying hens in Bogor Regency, Indonesia. Shells contaminated with many microorganisms will increase the risk of microbial penetration into eggs.…”
Section: S Aureus Contamination In Eggs and Egg Products In Indonesiamentioning
confidence: 99%
“…It can be obtained through mutations in its DNA alone or DNA acquisition that delivers resistance from another source [47]. Based on the results of the study [39], part big S. aureus isolates obtained from a cloacal swab farm chicken meat and egg laying in Bogor are resistant to tetracycline, ampicillin, oxytetracycline, erythromycin, and acid nalidixic. This study aimed to identify resistance genes, including blaTEM, gyrA, and tetA, found in S. aureus=Staphylococcus aureus animal husbandry, whereas ermB was only found on farm chicken broilers.…”
Section: S Aureus and Methicillin-resistant S Aureus (Mrsa)mentioning
confidence: 99%
“…Gen blaTEM (gen resistansi terhadap Amoksisilin) dideteksi dengan proporsi yang tinggi pada isolat asal manusia (100%), lingkungan (100%) dan hewan (85,5%) yang konsisten dengan hasil uji resistansi terhadap Amoksisilin dan Ampisilin. Identifikasi gen blaTEM pada sampel hewan, manusia, maupun lingkungan sebelumnya juga sudah pernah dilaporkan (Lenart-Boron et al, 2020;Hardiati et al, 2021;Hermana et al, 2021;Juwita et al, 2022). Gen blaTEM terletak dalam plasmid dan mengkodekan Extended-Spectrum β-Lactamase (ESBL), yaitu enzim yang mampu menghidrolisis Penisilin, Sefalosporin generasi satu, dua dan tiga, serta Aztreonam (Kaur et al, 2013).…”
Section: Gen Penyandi Resistansi Antibiotikunclassified
“…Pada E. coli, keberadaan gen tetA telah banyak dilaporkan di peternakan babi dengan proporsi tinggi (Kallau 2019;Petrin et al, 2019;Park dan Ham, 2020), pada unggas (Kurnia et al, 2018;Jahantigh et al, 2020;Hardiati et al, 2021), dan E. coli dari daging babi dan sapi (Sacher-Pirklbauer et al, 2021). Gen tetA juga dilaporkan pada isolat Staphylococcus aureus yang resistan terhadap Tetrasiklin (Hermana et al, 2021;Juwita et al, 2022).…”
Section: Gen Penyandi Resistansi Antibiotikunclassified
“…A comparable investigation was undertaken in Addis Ababa, Ethiopia, when 12.9% of S aureus was recovered from chicken cloacal swabs [15]. In a comparable research performed in Bogor Regency, Indonesia, 28% of S. aureus was retrieved from broiler chicken cloacal swabs and 50% was isolated from layer chicken cloacal swabs [16]. Our outcome was lower than those obtained from cloacal swabs of birds sold at five wholesale chicken outlets in Dhaka, Bangladesh (72%) and a broiler farm in Duhok, Iraq (80%) [17,18].…”
Section: Introductionmentioning
confidence: 97%